Clinical characterization and mutation spectrum of German patients with familial hypercholesterolemia. (October 2016) - Grenkowitz, Thomas; Kassner, Ursula; Wühle-Demuth, Marion; Salewsky, Bastian; Rosada, Adrian; Zemojtel, Tomasz; Hopfenmüller, Werner; Isermann, Berend; Borucki, Katrin; Heigl, Franz; Laufs, Ulrich; Wagner, Stephan; et al.
Abstract: Background and aims: Autosomal-dominant familial hypercholesterolemia (FH) is characterized by elevated plasma levels of low-density lipoprotein cholesterol (LDL-C) and a dramatically increased risk to develop cardiovascular disease (CVD). Mutations in three major genes have been associated with FH: the LDL receptor gene ( LDLR ), the apolipoprotein B gene ( APOB ), and the proprotein convertase subtilisin/kexin 9 gene ( PCSK9 ). Here we investigated the frequency and the spectrum of FH causing mutations in Germany. Methods: We screened 206 hypercholesterolemic patients, of whom 192 were apparently unrelated, for mutations in the coding region of the genes LDLR, PCSK9 and the APOB [c.10580G > A (p.Arg3527Gln)]. We also categorized the patients according to the Dutch Lipid Clinic Network Criteria (DLCNC) in order to allow a comparison between the mutations identified and the clinical phenotypes observed. Including data from previous studies on German FH patients enabled us to analyse data from 479 individuals. Results: Ninety-eight FH causing variants were found in 92 patients (nine in related patients and 6 patients with two variants and likely two affected alleles), of which 90 were located in the LDLR gene and eight mutations were identified in the APOB gene (c.10580G > A). No mutation was found in the PCSK9 gene. While 48 of the LDLR mutations were previously described as disease causing, we found 9 new LDLR variants which were rated as "pathogenic" or "likely pathogenic" based on the predicted effect on the corresponding protein. The proportions of different types of LDLR mutations and their localization within the gene was similar in the group of patients screened for mutations here and in the combined analysis of 479 patients (current study/cases from the literature) and also to other studies on the LDLR mutation spectrum, with about half of the variants being of the missense type and clustering of mutations in exons 4, 5 and 9. The mutation detection rate in the 35 definite and 45 probable FH patients (according to DLCNC) was 77.1% and 68.9%, respectively. The data show a similar discriminatory power between the DLCNC score (AUC = 0.789 (95% CI 0.721–0, 857)) and baseline LDL-C levels (AUC = 0.799 (95% CI = 0.732–0.866)). Conclusions: This study further substantiates the mutation spectrum for FH in German patients and confirms the clinical and genetic heterogeneity of the disease. Highlights: 206 patients were screened for mutations in the genes LDLR, PCSK9 and APOB . 98 FH causing variants were found in 92 patients. 9 new "pathogenic" or "likely pathogenic" LDLR variants were identified. The mutation detection rate was 77.1% in definite FH patients (DLCN criteria). DLCNC score and LDL-C levels showed equal capacity to predict mutation carriership.